2021
DOI: 10.1371/journal.pone.0253045
|View full text |Cite
|
Sign up to set email alerts
|

The p16/ki-67 assay is a safe, effective and rapid approach to triage women with mild cervical lesions

Abstract: Objective The aim of this study was to evaluate the diagnostic accuracy and efficiency of p16/ki-67 dual stain in the identification of CIN2+ lesions, in Greek women with ASCUS or LSIL cytology. Methods A total of 200 women, 20 to 60 years old, were enrolled in the study. All samples were cytologically evaluated and performed for p16/ki-67 and high-risk HPV (HR-HPV) test. All patients were referred to colposcopy for biopsy and histological evaluation. Three cervical cancer (CC) screening strategies were desi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
5
0
3

Year Published

2022
2022
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 7 publications
(8 citation statements)
references
References 36 publications
0
5
0
3
Order By: Relevance
“…A recent study of Beyzit et al found HPV58 to be the most abundant HPV type in their sample pool, second to HPV16 18 . Additionally, a study in a Greek female population found HPV31 to be the second most abundant HPV type, following HPV16 19 . In addition, a global geographical distribution analysis of HPV associated CC cases showed various distribution of different HPV types.…”
Section: Discussionmentioning
confidence: 95%
See 1 more Smart Citation
“…A recent study of Beyzit et al found HPV58 to be the most abundant HPV type in their sample pool, second to HPV16 18 . Additionally, a study in a Greek female population found HPV31 to be the second most abundant HPV type, following HPV16 19 . In addition, a global geographical distribution analysis of HPV associated CC cases showed various distribution of different HPV types.…”
Section: Discussionmentioning
confidence: 95%
“…The positive expression for p16/Ki-67 has proven to be extremely important in triaging patients diagnosed with ASC-US/LSIL, or non-HPV16/18 hrHPV types. 19,22 Despite strong evidence, only 10% of patients (216 cases) had an available dual staining for p16/Ki-67, meaning that the clinician did not consider necessary and/or did not order a dual staining test.…”
Section: Overexpression Of Cell Cycle Markers P16/ki-67 In Hrhpv Pati...mentioning
confidence: 99%
“…Because distinguishing low-grade from high-grade lesions can help avoid overtreatment, different biomarkers are being explored to better assist the grading of lesions. For example, a combination of biomarkers, such as p16 and K i -67 dual staining, could be used as an adjunctive test to improve the diagnostic accuracy of histopathology and detect CIN2+ among women with mild cervical lesions ( 18 , 19 ). Adding HPV E4 immunohistochemistry to p16 and grading the expression of these two markers helps to identify the heterogeneity of HSILs ( 20 ).…”
Section: Discussionmentioning
confidence: 99%
“…Коэкспрессия p16 и Ki-67 в одной клетке демонстрирует дисфункцию и наблюдается только в эпителии с интраэпителиальным поражением клеток, трансформированных ВПЧ. В клетках без интраэпителиального поражения экспрессия белков p16 и Ki-67 взаимоисключающая [50].…”
Section: исследование на вирус папилломы человекаunclassified
“…Ряд исследований показал диагностическую эффективность теста с двойным окрашиванием p16/Ki-67 [50−52]. Двойное окрашивание p16/Ki-67, с результатами цитологии ASC-US (atypical squamous cells of undetermined significance -атипичные клетки плоского эпителия неопределенного значения) или L-SIL (low-grade squamous intraepithelial lesion -плоскоклеточное интраэпителиальное поражение низкой степени), показало аналогичную чувствительность и значительно более высокую специфичность, чем тестирование на ВПЧ при сортировке ASC-US и LSIL [50], а также у женщин с нормальным Пап-тестом, но с положительным результатом ВПЧ-тестирования [53].…”
Section: исследование на вирус папилломы человекаunclassified